A retrospective cohort study investigating risk factors for the failure of Thoroughbred racehorses to return to racing after superficial digital flexor tendon injury. (May 2018) - Tamura, N.; Kodaira, K.; Yoshihara, E.; Mae, N.; Yamazaki, Y.; Mita, H.; Kuroda, T.; Fukuda, K.; Tomita, A.; Kasashima, Y.
Highlights: A retrospective cohort study of Thoroughbred flat racehorses with superficial digital flexor tendon injury was performed. Forty-nine of 346 (14.2%) racehorses successfully returned to racing. A higher number of injured tendon zones was the only risk factor significantly associated with failure to return to racing. Longer lesions presented a significantly increased risk of failure to successful return to racing. Abstract: A retrospective cohort study was conducted to investigate risk factors for the failure of Thoroughbred racehorses to return to racing after an injury of the superficial digital flexor tendon (SDFT). Successful return was defined as the completion of five or more races after SDFT injury. The official Japan Racing Association (JRA) medical records of racehorses with a core-type SDFT injury were reviewed for clinical variables related to the characteristics of the horse and the severity of SDFT injuries at the time of diagnosis. Data on racing outcomes were obtained from the official JRA racing database. Risk factors were screened using univariable logistic regression and subsequent multivariable model building. Forty-nine of 346 (14.2%) horses successfully returned to racing after SDFT injuries. Multivariable model building revealed that an increase in the total number of injured zones (defined as the total number of zones in which the injured hypoechoic area was observed at the time of ultrasonographic diagnosis of SDFT injury) was associated with an increased risk of failure to return to racing after SDFT injury. Horse characteristics, such as age, body mass and sex, were not associated with a successful return to racing. In the rehabilitation of cases with larger (longer) lesions, more effective and careful medical management may be needed for an improvement in the athletic outcomes.